Optimization of Container Freight Station Performance Through Operational Improvements at PT. Terminal Petikemas Surabaya - Augustinus, Brilian Gregory; Sudirman, Sudirman; Nasihah, Ainun (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2025)
Container Freight Station (CFS) is a crucial facility in supporting the efficiency of unloading operations and customs inspections for imported containers. At PT Terminal Petikemas Surabaya, a significant increase in activity between December 2024 and January 2025 led to an imbalance between delivery job volumes and service capacity, disrupting operational effectiveness. This study aims to identify operational constraints in CFS and propose appropriate optimization strategies. A descriptive qualitative method was employed, utilizing interviews, direct observation, and literature review. The findings indicate that key obstacles include limited unloading equipment, workforce shortages, and a lack of integrated information systems among work units. Recommended improvements involve adding work shifts during peak seasons, implementing regular equipment maintenance, enhancing interdepartmental coordination, and developing integrated IT systems. These efforts are expected to enhance operational efficiency and strengthen the competitive position of port logistics services.